Implementasi Wireless Sensor Node untuk Pemantauan Lahan Pertanian Berbasis Protokol 802.15.4 - Muhammad Misbahul Munir; Sabriansyah Rizqika Akbar; Adhitya Bhawiyuga (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Wireless Sensor Nodes is the main element in Wireless Sensor Network (WSN). Farmers can find out the condition of farmland by using WSN to handle the land appropriately. On WSN, IEEE 802.15.4 Protocols more suitable to monitor farmland because it has a 40% improvement in energy efficiency compared to IEEE 802.11. To form the WSN with tree topology, it takes 3 types of nodes, i.e. End device, the Coordinator, and the PAN Coordinator. Each node consists of the Arduino Nano and MRF24J40MA that uses communication SPI. In the End device the results data captured by temperature, humidity, and soil moisture sensors are different with data from measurement device. The position of node placement affected on performance of wireless sensor node. Based on packet loss, maximum distance in the transmission of sensor data is 104 metres from the End device to the Coordinator and 96 metres from Coordinator to the PAN Coordinator. The optimal distance is 72 meters of the End device to the Coordinator. Each transmission of sensor data is carried out every 10 seconds with 17 bytes of data payload.